2015
DOI: 10.19030/jabr.v31i2.9148
|View full text |Cite
|
Sign up to set email alerts
|

Bank Credit And Agricultural Output In South Africa: Cointegration, Short Run Dynamics And Causality

Abstract: In this paper we investigate the dynamic relationship between bank credit and agricultural output in South Africa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…Joseph Chisasa and Daniel Makina (2015) shows that there is a positive and significant relationship between bank credit, capital formation and agricultural output in South Africa [8]. The empirical results of this study indicate that, in the short term, capital formation has a positive and significant effect on agricultural output.…”
Section: Government Policy On Agricultural Creditmentioning
confidence: 61%
“…Joseph Chisasa and Daniel Makina (2015) shows that there is a positive and significant relationship between bank credit, capital formation and agricultural output in South Africa [8]. The empirical results of this study indicate that, in the short term, capital formation has a positive and significant effect on agricultural output.…”
Section: Government Policy On Agricultural Creditmentioning
confidence: 61%
“…Accordingly, 17% of the difference between long-term, equilibrium, or the desired amount of agricultural GDP and the current or observed agricultural GDP is reduced each year. Findings in the literature show that agricultural credits positively affect agricultural productivity (SHAH et al, 2008;AYAZ & HUSSAIN, 2011;SALEEM & JAN, 2011;AGUNUWA et al 2015;AWOTIDE et al 2015;CHISASA & MAKINA, 2015;NNAMOCHA & EKE, 2015;UDOKA et al 2016;OGBUABOR & NWOSU, 2017;DURAMAZ & TAS, 2018;ADEMOLA, 2019;TAMBI & BIME, 2019). IQBAL et al (2003), SIAL et al (2011, REHMAN et al (2017), KOC et al (2019); REHMAN et al (2019), found that agricultural credits have a positive and statistically significant effect on agricultural GDP.…”
Section: Ols Regression For Parameter Relationsmentioning
confidence: 99%
“…In equation (9), all the presumptive sign are correctly signed and the t-statistics were all significant at the one percent level of significance. In equation (10), all the variables apart from interest rate are all correctly signed. Interest rate, percentage of agriculture credit to total credit and percentage of non-oil export to total export are significant of at 5 percent level of significant.…”
Section: The Results Analysismentioning
confidence: 99%